PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK DI SMP NEGERI 1 LUBUK SIKAPING - Anggraini, Popi Alisia (Departemen Matematika, 2024)
As a student of mathematics, you should eventually become proficient at solving mathematical problems. Having said that, eighth graders at SMP Negeri 1 Lubuk Sikaping are woefully unprepared when it comes to addressing mathematical difficulties. One effective strategy for student improvement is to implement the Problem Based Learning (PBL) approach to education. Nonequivalent posttest-only control groups are a type of quasi-experiment that was used in this investigation. The research subjects were eighth graders from SMP Negeri 1 Lubuk Sikaping. Students from Classes VIII.11 and VIII.10 were chosen at random to make up the sample. The research instruments utilized for data analysis included tests for normality, homogeneity, and hypothesis testing; the last test included mathematical problem-solving. A t-test was performed on the data, and the result was a p-value of 0.005. If the p-value is less than the significance level α = 0.05, the null hypothesis (H_0) is rejected. The PBL-using eighth graders at SMP Negeri 1 Lubuk Sikaping outperformed their non-PBL-using peers in the traditional learning paradigm.Keywords– Problem Based Learning, Mathematical Problem Solving Skills, Conventional Learning